The Mahabharata: Vol. 2 - John B Chethimattam (Journal of Dharma, 1976)
One of the major projects undertaken in recent times for commu- nicating the Wisdom of the East to the West is the translation into English of the Mahabharata, the monumental epic about India's Great War, from the Sanskrit original running into about 100,000 couplets. This is a very important undertaking since the Mahabharata brings the Indian philosophical and religious ideals from the hoary heights of Vedic thinkers and Upanishadic sages down to the level of the concrete experience of the common man, in the form of legends and folklore, in the exercise of the duties of the warrior class and of the ordinary householder. The central story, the momentous war between the Kauravas and Pandavas takes place in Kurukshetra. This theme has not only deep roots in the history and the socio- logical evolution of the Indian nation, but also enduring religious significance since it points to the fight between good and evil in the battlefield of the human mind. An accurate and readable transla- tion was a long felt need since the available translations date from the last century, and a reliable, scientifically prepared critical edition of the original Sanskrit text was made available only in the recent past.